Options for Improving Nitrogen Utilization Efficiency in Ruminants - Paul, S. S.; Chanu, Y. M.; Dey, A. . (Indian Journal of Animal Nutrition, 2018)
Protein sources are high cost component of animal diet and efficiency of utilization of dietary protein in ruminants is about 5 to 30%. Ammonia emission from livestock is a serious environmental concern. Several complex models for predicting protein requirement have been introduced but predictability of response to dietary protein is still low. In this paper, an attempt has been made to review various scientific leads that can help in improving efficiency of protein utilization in ruminants including further researchable areas where clarity is lacking. In India, more efforts need to be made to estimate post-ruminal degradability of proteins, assess N recycling, estimate amino acid composition of protein sources and efficiency of utilization of absorbed amino acids. Extensive studies should also be undertaken on different functional groups of microbes especially hyper-ammonia producing bacteria and their interaction with fibre degrading bacteria using modern high throughput molecular biology tools and efforts need to be made to integrate molecular-based rumen microbial ecology with dietary conditions to allow us to better explain and,therefore, predict conditions that will improve N utilization efficiency. In the long run, development of efficient animals and plant breeding strategy for development of high sugar forages should also be considered. Hence, making use of available knowledge regarding different aspects of protein nutrition can significantly improve N utilization efficiency and reduce adverse impact on environment.